Change Management in Faith-Based University Transformation: A Case Study of Aisyiyah Higher Education - M. Aditya Salam; Saipul Annur; Afriantoni Afriantoni (MASI Mandiri Edukasi, 2026)
Institutional transformation in higher education has become unavoidable in response to regulatory changes, organizational demands, and socio-cultural developments in the Society 5.0 era. In Indonesia, private universities affiliated with faith-based organizations face additional challenges in governance, cultural integration, and institutional legitimacy. This study investigates the transformation process of Aisyiyah higher education institutions through a case study of Universitas Aisyiyah Palembang, which evolved from a health-focused college into a comprehensive university. The research aims to examine change management practices, identify internal and external challenges, and evaluate strategic initiatives undertaken during the transformation process. A qualitative approach was used, including in-depth interviews, observations, and document analysis, to explore organizational experiences and leadership strategies. The findings indicate that institutional change followed a structured process involving preparation, transition, and stabilization phases. Key obstacles included financial constraints, human resource readiness, regulatory compliance, and cultural adaptation. These challenges were addressed through collegial leadership, strategic institutional development, and the internalization of Al-Islam and Kemuhammadiyahan values as a foundation for organizational sustainability. The study concludes that successful institutional transformation requires strong leadership commitment, cultural alignment, and long-term strategic planning.